Fit between decision mode and processing style predicts subjective value of chosen alternatives. (25th July 2016) - Dijkstra, Koen A.; van der Pligt, Joop; van Kleef, Gerben A.
Abstract: Intuition is associated with a global processing style, whereas deliberation is associated with a local processing style. Drawing on previous research on the effects of decisional fit on the subjective value attached to chosen alternatives, we examined the possibility that a fit between processing style and decision mode results in greater subjective value than a lack of fit. In three experiments employing various combinations of naturally occurring and experimentally manipulated processing styles and decision modes, we found that when congruence was high (i.e., global processing style and intuitive judgment, or local processing style and deliberative judgment), participants judged their chosen item to be more expensive than when congruence was low. These findings indicate that increased fit resulted in higher estimated value. We discuss implications for judgment and decision‐making.